Chemical Compositions of Dew and Scavenging of Particles in Changchun, China. (21st May 2015) - Xu, Yingying; Zhu, Hui; Tang, Jie; Lin, Yingzi
Abstract : Dew and rain water were collected during 2013 and 2014 in Changchun, China. The dew was analyzed and the following parameters were measured: pH, EC, TDS, major anions (F −, Cl −, SO 4 2 -, and NO 3 - ), and major cations (NH 4 +, Na +, K +, Ca 2+, and Mg 2+ ). The mean pH, EC, and TDS values of dew were comparable with the values for rainwater. The pH values of dew and rain were 6.72 and 6.16, respectively. Both EC (308 μ S/cm) and TDS (154 mg/L) of dew were higher than those in rain samples. The concentration of main ions in dew was 1.5–5.7 times higher than levels in rainwater. The near-neutral pH values in dew were caused by the neutralization of acidity and buffering by the alkaline elements of soil origin (Ca 2+ ). This neutralization was confirmed by a strong correlation between the acidic ions (SO 4 2 - and NO 3 - ) and the major cations (Ca 2+ and Mg 2+ ). Natural dust made an important contribution to the ions present in dews, but the presence of sulfate concentrations that are notably higher than rain water (up to 1584.5 μ eq/L) indicated a significant contribution of anthropogenic sources. Dew has the ability to capture particulates, and the purifying effect on the underlying surface was obvious.